Navigating cultural contexts: How multinational corporations shape CSR strategies in Nepal - Sthapit, Arhan; Bhattarai, Ujjwal; Timsina, Baburam; Kayestha, Mijala (American Journal of STEM Education, 2025)
This study examines the key cultural factors that influence the prioritization and implementation of corporate social responsibility (CSR) initiatives by multinational corporations (MNCs) operating in Nepal. This study used an interpretive qualitative approach and an exploratory multiple-case study method. Five MNCs from several industry sectors were selected purposively, and a semi-structured interview was conducted with top-level executives and managerial employees. The interview was transcribed, coded, and thematized using the free trial version of MAXQDA. Five major themes emerged from analyzing participant transcripts: cultural norms and values, cultural timing, cultural dynamics, cultural sensitivity, and resource allocation. By showing the multidisciplinary value of understanding how cultural dynamics influence CSR decision-making, the study bridges the knowledge gap between CSR and cultural studies in the context of developing nations.